Strategi Pembinaan Organisasi Kemahasiswaan Intra Kampus Di UIN Raden Intan Lampung - Tuala, Riyuzen Praja; Septuri, Septuri; Fradito, Aditia (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research aims to describe the strategy of fostering intra-campus student organizations at Raden Intan Lampung State Islamic University. This research includes a type of qualitative descriptive research. The main data source was obtained from informants consisting of Vice Rector III and Vice Dean III from six Faculties and one of the staff of the student and academic section of Raden Intan Lampung State Islamic University. Data collection methods include in-person interviews, non-participant observations and documentation. Data analysis techniques consist of data reduction, data presentation and conclusion withdrawal. Data validity tests are used source triangulation techniques and triangulation methods. The results showed there are five strategies for fostering intra-campus student organizations at Raden Intan Lampung State Islamic University: First, institutional development strategy. Second, The Strategy of Coaching the Field of Reasoning and Science. Third, The Construction Strategy of Areas of Interest, Talent and Favorites. Fourth, the Development Strategy for Welfare. Fifth, the Strategy of Development in the Field of Cooperation. Keywords: Intra-Campus Student Organization, Development, Strategy Penelitian ini bertujuan mendeskripsikan strategi pembinaan organisasi kemahasiswaan intra kampus di UIN Raden Intan Lampung. Penelitian ini termasuk jenis penelitian deskriptif kualitatif. Sumber data pokok didapat dari para informan yang terdiri atas Wakil Rektor III dan para Wakil Dekan III dari enam Fakultas dan salah satu staf bagian kemahasiswaan dan akademik UIN RIL. Metode pengumpulan data meliputi wawancara langsung, observasi non partisipan dan dokumentasi. Teknik analisis data terdiri atas reduksi data, penyajian data dan penarikan kesimpulan. Uji keabsahan data digunakan teknik triangulasi sumber dan triangulasi metode. Hasil penelitian menunjukkan terdapat lima strategi pembinaan organisasi kemahasiswaan intra kampus di UIN Raden Intan Lampung: Pertama, Strategi Pembinaan Bidang Kelembagaan. Kedua, Strategi Pembinaan Bidang Penalaran dan Keilmuan. Ketiga, Strategi Pembinaan Bidang Minat, Bakat dan Kegemaran. Keempat, Strategi Pembinaan Bidang Kesejahteraan. Kelima, Strategi Pembinaan Bidang Kerjasama.Kata kunci: Organisasi Kemahasiswaan Intra Kampus, Pembinaan, Strategi